Transition of complex permittivity losses in Hevea rubber latex from conductivity losses to dipolar losses at 2.6 GHz - Hassan J; Khalid K; Yusoff W M D Wan (Journal of Rubber Research, 2003)
Dielectric properties of Hevea rubber latex with moisture content 38;-98;were measured using the open-ended coaxial line sensor coupled to the Automated Network Analyser. Measurements were made at frequencies 0.2 GHz-20 GHz and at selected temperatures -30oC to 50oC. Complex permitivity losses or dielectric loss factor showed a very interesting phenomena at 0.2 GHz to 2.6 GHz where a transition occured from conductivity losses to dipolar losses. Below 2.6 GHz, the losses were due to the conducting phases in the Hevea latex arising from proteins, fatty acid soaps, phospholipids and various types of ohmic species. Higher losses were achieved from latex concentrate due to the addition of ammonia as preservative. Above 2.6 GHz the losses were governed by orientation of the water molecules. The transition was clearly observed in the plots of dielectric losses versus temperature at 0.2, 0.6, 1.0, 1.4, 1.8, 2.2 and 2.6 GHz for latex concentrate, fresh latex, diluted fresh latex and deionised water at moisture contents 38;, 56;, 89;and 100;, respectively.
Keywords: Conductivity; Dielectric; Dipolar; Hevea brasiliensis; Latex; Loss; Moisture content; Permittivity; Properties; Temperature; Transition